Eya1 gene dosage critically affects the development of sensory epithelia in the mammalian inner ear - Zou, Dan (Oxford University Press, 2008)
Haploinsufficiency of the transcription co-activator EYA1 causes branchio–oto–renal syndrome, congenital birth defects that account for as many as 2% of profoundly deaf children; however, the underlying cause for its dosage requirement and its specific role in sensory cell development of the inner ear are unknown. Here, an allelic series of Eya1 were generated to study the basis of Eya1 dosage requirements for sensory organ development. Our results show different threshold requirements for the level of Eya1 in different regions of the inner ear. Short and disorganized hair cell sterocilia was observed in wild-type/null heterozygous or hypomorphic/hypomorphic homozygous cochleae. Patterning and gene-marker analyses indicate that in Eya1 hypomorphic/null heterozygous mice, a reduction of Eya1 expression to 21% of normal level causes an absence of cochlear and vestibular sensory formation. Eya1 is initially expressed in the progenitors throughout the epithelium of all six sensory regions, and later on during sensory cell differentiation, its expression becomes restricted to the differentiating hair cells. We provide genetic evidence that Eya1 activity, in a concentration-dependent manner, plays a key role in the regulation of genes known to be important for sensory development. Furthermore, we show that Eya1 co-localizes with Sox2 in the sensory progenitors and both proteins physically interact. Together, our results indicate that Eya1 appears to be upstream of very early events during the sensory organ development, hair cell differentiation and inner-ear patterning. These results also provide a molecular mechanism for understanding how hypomorphic levels of EYA1 cause inner-ear defects in humans.